REPLACEMENT OF WHEAT FLOUR WITH WHEAT BRAN FOR FLOATING FISH FEED PRODUCTION - Ismail, Safiya (Nigerian Journal of Fisheries, 2025)
Wheat bran does not only serve as raw material for animal feeds; it has also become a natural additive due to its high mineral contents such as calcium, sodium, potassium, iron, phosphorus etc. wheat flour has been used as binder which help in enhancing fish feed buoyancy for decades, This research examined the viability of replacing wheat flour with wheat bran for on-farm floating feed production aimed at reducing cost and improving environmental sustainability. Five feeds with replacing level of wheat flour by wheat bran at 0%, 25%, 50%, 75% and 100% were formulated at 30% and 40% crude proteins using Pearson Square method. Inferential statistics analysis using line graphs revealed significant differences (p<0.05) among treatments’ floatability rates. The results revealed that feed formulated at 30% crude protein floated for 55% at 75%WB/25%WF. This demonstrates the roles of starch at low crude protein level and also gluten in wheat flour that enhance the buoyancy of feed than a more fibrous feed of the wheat bran while 40% crude protein levels exhibited 40% floatation at 25%WB/75%WF. Low floatation rate recorded in this study could be attributed to high fibre content of the wheat bran, Both crude protein levels had 100% floatation at 100 wheat flour which floated for the whole 60 minutes period. It can be concluded that, wheat bran can replace wheat flour at 75% at 30% crude protein and 25% for 40% crude protein for producing floating fish feed beyond which feed buoyancy may not b